2003
DOI: 10.1002/j.2050-0416.2003.tb00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Three Sorghum Cultivars Used for the Production of Bili-Bili Beverage in Northern Cameroon

Abstract: The malting characteristics of sorghum malts produced locally in Cameroon for Bili-Bili brewing were compared with those of malts produced in a laboratory. The analytical values of both malts were similar but the brewing potential of the laboratory malts were marginally better than those of the locally produced malts. Of the three cultivars examined, Madjeru had the lowest levels of ␤-amylase, maltose levels and fermentability. The worts of the Madjeru filtered the slowest of the three malts. During malting ␤-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…Previous studies on malting and mashing of sorghum cultivars used in this study showed that Madjeru mashes filtered slower than those of Safrari and S.35 17,18 . This slow filtration rate was suggested to be due to the low amounts of α-amylase and β-amylase in Madjeru malts compared to Safrari and S.35.…”
Section: Resultsmentioning
confidence: 48%
See 4 more Smart Citations
“…Previous studies on malting and mashing of sorghum cultivars used in this study showed that Madjeru mashes filtered slower than those of Safrari and S.35 17,18 . This slow filtration rate was suggested to be due to the low amounts of α-amylase and β-amylase in Madjeru malts compared to Safrari and S.35.…”
Section: Resultsmentioning
confidence: 48%
“…Although the proportions of fermentable sugars of worts of the three cultivars were comparable, that of maltose was less than 50% for Madjeru, when compared with Safrari and S.35 17 . These observations were partly attributed to limited amounts of starch hydrolyzing enzymes such as α-amylase and β-amylase present in the Madjeru malts 17 . This is indeed one of the major problems encountered in mashing with some malted sorghum cultivars [3][4][5]8,9,13,14,17,18,21 .…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations